2020
DOI: 10.1039/d0ta02805c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Li substructure on the diffusion pathways in alpha and beta Li3PS4: an in situ high temperature neutron diffraction study

Abstract: An in situ variable-temperature neutron diffraction study of Li3PS4 reveals the structure and Li-ion diffusion pathways (via MEM and BVEL calculations) of the high temperature fast-ion conductor, α-Li3PS4, (Ea = 0.22 eV), and compares them to those of other polymorphs and the Si-substituted phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(108 citation statements)
references
References 42 publications
11
96
1
Order By: Relevance
“…in 2010 for bulk β‐Li 3 PS 4 at high temperature, [ 27 ] but in agreement with the recently suggested by Nazar et al. [ 5 ] The activation energies for Li + conduction were also determined for LC, MC, and HC samples from the Arrhenius‐like fitting (Equation (12) in Experimental Section) of their temperature dependent EIS spectra, these being 0.35, 0.37, and 0.39 eV, respectively, in line with the trend found for the ionic conductivity in such samples (Figure 9d).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…in 2010 for bulk β‐Li 3 PS 4 at high temperature, [ 27 ] but in agreement with the recently suggested by Nazar et al. [ 5 ] The activation energies for Li + conduction were also determined for LC, MC, and HC samples from the Arrhenius‐like fitting (Equation (12) in Experimental Section) of their temperature dependent EIS spectra, these being 0.35, 0.37, and 0.39 eV, respectively, in line with the trend found for the ionic conductivity in such samples (Figure 9d).…”
Section: Resultssupporting
confidence: 91%
“…[ 3,4 ] Further heating above 475 °C leads to the conversion into the highly conductive α‐phase, whose structure has been recently elucidated by neutron diffraction. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ XRD results show that α‐Li 3 PS 4 will directly generate γ‐Li 3 PS 4 without forming β phase during the cooling process, and its ion conductivity is only 3 × 10 −7 S cm −1 . Recently, Kaup et al 78 found that Si‐substituted Li 3.25 Si 0.25 P 0.75 S 4 can well stabilize the β‐phase structure and can still maintain β‐Li 3 PS 4 structure at 600°C (Figure 5(A)). In addition, Stöffler et al 79 found that some Li 4 P 2 S 6 phases will be formed during the heating process of Li 3 PS 4 , and the phenomenon of sulfur sublimation can be observed at ~660°C.…”
Section: Material‐level Thermal Stability Of Sesmentioning
confidence: 99%
“…In anti-perovskites, like Li 3 OCl, cation motion is largely vacancy driven(REFS), 45,46 with the displacement of a cation required before another cation can take its place and so, if the E a associated with a cation hop is large, very little transport occurs at all, correlated or otherwise. However, in Li 3 PS 4 (and other thiophosphate materials), a different mechanism has been proposed, namely, the so-called 'paddle-wheel effect', 47,48 which refers to the complex motion of polyanions that are able to undergo rotations that drive the concerted motion of cations. Even if the GBs have relatively little impact on the actual E a of cation transport, the change in the degree of correlation might lead one to assume that these polyanion rotations are inhibited in the vicinity of the boundary.…”
Section: Resultsmentioning
confidence: 99%